Social equity, resilience, and climate change adaptation: A sourcebook for program designers - Reyes-Sacdalan, Norcelita B.; Soriaga, Rowena; Cabriole, Marie Aislinn; Gonsalves, Julian; Hellin, Jon (2024)
Smallholder farmers, particularly women and the poor, are among the most vulnerable to the climate crisis, necessitating timely and appropriate adaptation solutions. Delayed or inadequate responses exacerbate their vulnerability, highlighting the need for equitable and inclusive climate resilience strategies. The CGIAR Initiative on Climate Resilience (ClimBeR) addresses these challenges by promoting science-based innovations to transform food, land, and water systems in six target countries: Guatemala, Kenya, Morocco, the Philippines, Senegal, and Zambia. ClimBeR aims to enhance smallholder resilience while ensuring gender equity and social inclusion.